Pengolahan Produk Turunan Cabai untuk Mengatasi Panen Raya Cabai di Desa Ringinanyar, Ponggok, Blitar, Jawa Timur - Muhamad Sapoan; Prayoga Suryadarma (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Ringinanyar Village is a village with a population of around 2416 people where one of the agricultural commodities is chili. chili prices during the main harvest tend to decrease due to the excess production of chili that exceeds market needs. This problem can be overcome by making a product derived from chili which has a relatively long shelf life and a relatively stable price. Among other chili derivative products are chili flour and instant chili seasonings with various flavors such as spicy, spicy chocolate, spicy cheese, spicy fish and spicy shrimp. Keywords: Blitar, chili, postharvest, Ringinanyar